An Assessment of How Nurse Practitioners Create Access to Primary Care in Canadian Residential Long-Term Care Settings - Nancy Carter, Esther Sangster-Gormley, Jenny Ploeg, Ruth Martin-Misener, Faith Donald, Abigail Wickson-Griffiths, Sharon Kaasalainen, Carrie McAiney, Kevin Brazil, Alan Taniguchi and Lori Schindel Martin (Nursing Leadership, 2016)
The aim of this paper is to explore the role and activities of nurse practitioners (NPs) working in long-term care (LTC) to understand concepts of access to primary care for residents. Utilizing the "FIT" framework developed by Penchanksy and Thomas, we used a directed content analysis method to analyze data from a pan-Canadian study of NPs in LTC. Individual and focus group interviews were conducted at four sites in western, central and eastern regions of Canada with 143 participants, including NPs, RNs, regulated and unregulated nursing staff, allied health professionals, physicians, administrators and directors and residents and family members. Participants emphasized how the availability and accessibility of the NP had an impact on access to primary and urgent care for residents. Understanding more about how NPs affect access in Canadian LTC will be valuable for nursing practice and healthcare planning and policy and may assist other countries in planning for the introduction of NPs in LTC settings to increase access to primary care.
Keywords: Nurse practitioner, access to care, long-term care, primary care